2016
DOI: 10.1002/hbm.23203
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific mediation effect of the right fusiform face area volume on the association between variants in repeat length ofAVPR1ARS3 and altruistic behavior in healthy adults

Abstract: Microsatellite variants in the arginine vasopressin receptor 1A gene (AVPR1A) RS3 have been associated with normal social behaviors variation and autism spectrum disorders (ASDs) in a sex-specific manner. However, neural mechanisms underlying these associations remain largely unknown. We hypothesized that AVPR1A RS3 variants affect altruistic behavior by modulating the gray matter volume (GMV) of specific brain regions in a sex-specific manner. We investigated 278 young healthy adults using the Dictator Game t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…However, in several studies, cathodal stimulation was associated with a neurobehavioral effect in agreement with an enhanced function of the cerebellar cortex (Galea et al, 2011 ; Ferrucci et al, 2012 ; Pope and Miall, 2012 ; Shah et al, 2013 ; Bersani et al, 2015 ; Bocci et al, 2015 ; Bradnam et al, 2015 ; Minichino et al, 2015 ; Panouillères et al, 2015b ). On the other hand some studies have shown that anodal stimulation may impair cerebellar function (Ferrucci et al, 2008 ; Foerster et al, 2013 ; Dutta et al, 2014 ; Macher et al, 2014 ; Bocci et al, 2015 ; Doeltgen et al, 2015 ; Panouillères et al, 2015b ; Chothia et al, 2016 ). For instance, Panouillères et al ( 2015b ) showed that cathodal cerebellar tDCS facilitates saccadic adaptation, while anodal tDCS disrupted the adaptation.…”
Section: Technical Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in several studies, cathodal stimulation was associated with a neurobehavioral effect in agreement with an enhanced function of the cerebellar cortex (Galea et al, 2011 ; Ferrucci et al, 2012 ; Pope and Miall, 2012 ; Shah et al, 2013 ; Bersani et al, 2015 ; Bocci et al, 2015 ; Bradnam et al, 2015 ; Minichino et al, 2015 ; Panouillères et al, 2015b ). On the other hand some studies have shown that anodal stimulation may impair cerebellar function (Ferrucci et al, 2008 ; Foerster et al, 2013 ; Dutta et al, 2014 ; Macher et al, 2014 ; Bocci et al, 2015 ; Doeltgen et al, 2015 ; Panouillères et al, 2015b ; Chothia et al, 2016 ). For instance, Panouillères et al ( 2015b ) showed that cathodal cerebellar tDCS facilitates saccadic adaptation, while anodal tDCS disrupted the adaptation.…”
Section: Technical Issuesmentioning
confidence: 99%
“…A sham session usually consists of ramping up the current to the same intensity as used in the active sessions, followed by immediately ramping down the current. In most studies this procedure results in an active stimulation of 30–60 s (Galea et al, 2009 ; Jayaram et al, 2012 ; Block and Celnik, 2013 ; Sadnicka et al, 2013 ; Chen et al, 2014 ; Dutta et al, 2014 ; Hardwick and Celnik, 2014 ; Herzfeld et al, 2014 ; Zuchowski et al, 2014 ; Benussi et al, 2015 ; Doeltgen et al, 2015 ; Martin et al, 2015 ; Panouillères et al, 2015a , b ; Chothia et al, 2016 ; Van Wessel et al, 2016 ; Wessel et al, 2016 ). To effectively blind the subjects for sham or active stimulation, the electrodes remain on the head after ramping down the current to obtain the impression of comparable session lengths.…”
Section: Technical Issuesmentioning
confidence: 99%
“…2015 ; Ryk etal. 2014 ), and a series of repeats in the AVPR1A gene’s promoter region, which have been associated with social behavior in voles, mice and humans ( Donaldson and Young 2013 ; Hammock and Young 2005 ; Wang etal. 2016 ; Walum etal.…”
Section: Introductionmentioning
confidence: 99%
“…Often researchers have examined three nucleotide repeats: two located in the 5′ promoter region (RS1, RS3) and one in the intron (AVR) of AVPR1A . In both patient and non-patient populations the lengths of these repeats have been shown to modulate social behaviors including altruistic behavior in healthy adults, prepulse inhibition, and the processing of facial expressions (Knafo et al, 2008; Levin et al, 2009; Zink and Meyer-Lindenberg, 2012; Wang et al, 2016). In an ASD sample, evidence of disequilibrium of the AVPR1A microsatellite RS3 was observed in 115 trios (Kim et al, 2002).…”
Section: Introductionmentioning
confidence: 99%